Pretransplant Recipient Circulating CD4+CD127lo/− Tumor Necrosis Factor Receptor 2+ Regulatory T Cells: A Surrogate of Regulatory T Cell–Suppressive Function and Predictor of Delayed and Slow Graft Function After Kidney Transplantation. Issue 2 (February 2016) - Nguyen, Minh-Tri J. P.; Fryml, Elise; Sahakian, Sossy K.; Liu, Shuqing; Cantarovich, Marcelo; Lipman, Mark; Tchervenkov, Jean I.; Paraskevas, Steven
Abstract : Background: Delayed graft function (DGF) and slow graft function (SGF) are ischemia-reperfusion–associated acute kidney injuries (AKI) that decrease long-term graft survival after kidney transplantation. Regulatory T (Treg) cells are protective in murine AKI, and their suppressive function predictive of AKI in kidney transplantation. The conventional Treg cell function coculture assay is however time-consuming and labor intensive. We sought a simpler alternative to measure Treg cell function and predict AKI. Methods: In this prospective observational cohort study, pretransplant recipient circulating CD4+CD25+CD127lo/− and CD4+CD127lo/− tumor necrosis factor receptor 2 (TNFR2)+ Treg cells were measured by flow cytometry in 76 deceased donor kidney transplant recipients (DGF, n = 18; SGF, n = 34; immediate graft function [IGF], n = 24). In a subset of 37 recipients, pretransplant circulating Treg cell–suppressive function was also quantified by measuring the suppression of autologous effector T-cell proliferation by Treg cell in coculture. Results: The TNFR2+ expression on CD4+CD127lo/− T cells correlated with Treg cell–suppressive function (r = 0.63, P < 0.01). In receiver operating characteristic curves, percentage and absolute number of CD4+CD127lo/−TNFR2+ Treg cell predicted DGF from non-DGF (IGF + SGF) with area under the curves of 0.75 and 0.77, respectively, and also AKI (DGF + SGF) from IGF with area under the curves of 0.76 and 0.72, respectively ( P < 0.01). Prediction of AKI (DGF + SGF) from IGF remained significant in multivariate logistic regression accounting for cold ischemic time, donor age, previous transplant, and pretransplant dialysis modality. Conclusions: Pretransplant recipient circulating CD4+CD127lo/−TNFR2+ Treg cell is potentially a simpler alternative to Treg cell function as a pretransplant recipient immune marker for AKI (DGF + SGF), independent from donor and organ procurement characteristics. Abstract : Supplemental digital content is available in the text.